PEMASARAN SYARIAH PADA LEMBAGA KEUANGAN MIKRO SYARIAH - Adinugraha, Hendri Hermawan (IAIN Tulungagung, 2017)
Abstract: The rise of sharia fnance industry that used âsharia brandingâÂ such as sharia banking, sharia mini market, sharia hotel, until sharia franchiseÂ resulted in conventional institutions are also diversifying sharia-compliant.Â Ideally this should be balanced by the application of such management isÂ based on sharia like sharia marketing, but in reality many of them areÂ not implementing it yet. Based on the above reasons, this research aims toÂ understand the concept and implementation of sharia marketing at MicroÂ Islamic Financial Institutions (Puskopsyah DIY) comprehensively. This studyÂ used a type of feld research that is descriptive analytical. This study is alsoÂ equipped with library research. Data collection techniques using triangulationÂ method, while the data analysis techniques using taxonomic analysis withÂ interactive model. The survey results revealed that implementation of shariaÂ marketing concept in Puskopsyah DIY was good enough though not all aspectsÂ of running perfectly. For example, the facts on the ground show that not allÂ product marketing process carried out by the prevailing fatwa supervised andÂ issued by the Sharia Supervisory Board.Keywords: Sharia, Marketing, and Puskopsyah DIY.